Optimizing Mother’s Role in Preventing Radicalism - Adila, Nesria; Oktavia, Gifa; Febriani, Afifah; Datres, Datres (Sekolah Tinggi Agama Islam YDI Lubuk Sikaping, 2024)
The dangers and threats of radicalism are increasingly lurking in the younger generation today. An ideology created and formed by a group of people who want instant and drastic change by using violent means and in the name of religion even though it is against the law and religion. This is where the role of women is very strong in the lives of their children, especially in Minangkabau culture, women's position can be optimized in preventing radicalism. Researchers use qualitative research methods. Where researchers carefully and carefully examine an activity, be it an event, activity, process, or group of individuals in a predetermined time and area. The mother's role as a madrasah ula can be seen from the extraordinary intensity of time between the child and the mother. From the mother, children's education begins, learning something new in their life, learning to speak, gaining knowledge, and forging their personality in living their life. Optimizing the role of mothers can be done by collaborating with government programs such as marriage programs, marriage counseling, and holding mosque youth weddings, recitations for mothers, religious lectures, and pre-marital education. As well as incorporating parenting patterns into learning material.